2023
DOI: 10.1017/pds.2023.15
|View full text |Cite
|
Sign up to set email alerts
|

A Follow-Up on the Methodical Framework for the Identification, Analysis and Consideration of Uncertainty in the Context of the Integration of Sensory Functions by Means of Sensing Machine Elements

Abstract: When integrating sensing machine elements for in-situ measurements in technical systems, special attention must be paid to uncertainty to ensure the reliability of the provided information. Therefore, a methodical framework for the identification, analysis and consideration of uncertainty was already developed in prior research, which still offers room for improvement regarding the included methods and tools. Therefore, in this contribution, the initially proposed methods and tools are adapted and extended to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Therefore, a filter option can be used to discard all results that include physical effects that do not occur in the considered system. (Welzbacher et al, 2022;Welzbacher et al, 2023) In the next step, identified data and model uncertainty is evaluated in a modified Failure-Mode and Effects-Analysis (FMEA) to determine its criticality for the reliability of the data provided by the sensory function. Uncertainty is evaluated in this context using three different criteria:…”
Section: Methodical Framework For the Identification Analysis And Con...mentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, a filter option can be used to discard all results that include physical effects that do not occur in the considered system. (Welzbacher et al, 2022;Welzbacher et al, 2023) In the next step, identified data and model uncertainty is evaluated in a modified Failure-Mode and Effects-Analysis (FMEA) to determine its criticality for the reliability of the data provided by the sensory function. Uncertainty is evaluated in this context using three different criteria:…”
Section: Methodical Framework For the Identification Analysis And Con...mentioning
confidence: 99%
“…The evaluation schemes range from 1 to 5, where 1 means a small and 5 a significant severity, deviation or impact. (Welzbacher et al, 2022;Welzbacher et al, 2023) Based on the results of the evaluation, a reasoned decision can be made whether or not an uncertainty is critical for the reliability of the data provided by the sensory function. Therefore, rigid threshold values are used that are oriented at, e.g., the maximum permissible measuring error of the sensory function.…”
Section: Methodical Framework For the Identification Analysis And Con...mentioning
confidence: 99%
See 3 more Smart Citations